دعم الخدمات الصحية الخضراء للحد من الآثار البيئية في القطاع الصحي - البسكري, أيوب المنتصر عبدالحفيظ; طوبى, عبدالسلام سالم (Al-Qurtas, 2026)
دعم الخدمات الصحية الخضراء للحد من الآثار البيئية في القطاع الصحي